Techno-economic analysis of caffeine and catechins production from black tea waste - SARIYAR AKBULUT, BERNA; KAZAN, DİLEK; SAYAR, NİHAT ALPAGU; PİNAR, ORKUN; DURMAZ ŞAM, SELÇEN (ELSEVIER, 2019)
y This work establishes a proof of concept level economic assessment of a novel commercial production scheme for caffeine and catechins from black tea waste collected in the north-eastern region of Turkey. A base case in which dichloromethane (DCM) is used as the product extracting agent and an alternative greener case where DCM is replaced with environmentally friendlier ethyl acetate (EA) were designed and modelled on Superpro Designer platform. Profitability analyses were conducted for both cases, each treating 30,000 MT/year of black tea waste. Under the base case scenario, the Net Present Value (NPV) was calculated as 16,249,000 USD whereas the alternative scenario gave an NPV of 4,379,000 USD with corresponding payback times of 5.64 and 6.79 years. A novel techno-economic evaluation method involving the metamodeling of Superpro Designer models via Kriging and subsequent multi-objective optimization is incorporated into the economic assessment and applied to the two cases in order to optimize selected dominant process variables. Optimal values for dominant operating process variables were found using 3-D graphs simulating the combined effects of these variables on NPV. Results showed that the base case has a greater potentiality to generate profit. However, the greener case could be implemented if it is supported on environmental and toxicity issues considering the potential health and pollution preventive benefits. The present work demonstrates how the integration of novel conceptual design, modelling, and optimization approaches can foster broader evaluation of bioprocesses utilizing negative-value agro-wastes for the production of value-added chemicals. (C) 2019 Institution of Chemical Engineers. Published by Elsevier B.V. All rights reserved.
Keywords: Bioprocess design; Techno-economic analysis; Caffeine; Catechins; Black tea waste; Kriging; EXTRACTION; OPTIMIZATION